2020
DOI: 10.1039/d0ja00340a
|View full text |Cite
|
Sign up to set email alerts
|

Highly depth-resolved characterization of fusion-related tungsten material based on picosecond laser-induced breakdown spectroscopy

Abstract: The objective of the present study is to evaluate the potential applications of picosecond Laser-Induced Breakdown Spectroscopy (ps-LIBS) in the nuclear fusion devices. The laser ablation behaviors and the spectral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Many studies focus on using LIBS to monitor material deposition or H isotope penetration into PFCs. [332][333][334][335][336] Mittelmann et al 332 used fs-LIBS along with calibration-free approaches to quantify D in W materials. Zhao et al 334 investigated ps-LIBS, finding that the lowest energy ablation regime resulted in the optimal W signal and a minimal ablation rate, providing very high-resolution depth profiling capabilities.…”
Section: Fusion Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focus on using LIBS to monitor material deposition or H isotope penetration into PFCs. [332][333][334][335][336] Mittelmann et al 332 used fs-LIBS along with calibration-free approaches to quantify D in W materials. Zhao et al 334 investigated ps-LIBS, finding that the lowest energy ablation regime resulted in the optimal W signal and a minimal ablation rate, providing very high-resolution depth profiling capabilities.…”
Section: Fusion Reactorsmentioning
confidence: 99%
“…[332][333][334][335][336] Mittelmann et al 332 used fs-LIBS along with calibration-free approaches to quantify D in W materials. Zhao et al 334 investigated ps-LIBS, finding that the lowest energy ablation regime resulted in the optimal W signal and a minimal ablation rate, providing very high-resolution depth profiling capabilities. Hai et al 337 investigated the LIBS spectral response to sample temperature and found the signal to be enhanced at high temperatures, which would be advantageous for in situ monitoring of PFCs during operation.…”
Section: Fusion Reactorsmentioning
confidence: 99%
“…163 Tungsten-based material properties were the focus of multiple publications. Picosecond LIBS was investigated by Zhao et al for high depth resolution diagnosis of W. 164 Three ablation regimes in laser uence were identied based on average ablation rate changes and surface morphology variations, with SEM used to investigate crater morphologies and microstructures from the three regimes. One regime was identied as superior based on the limited average ablation rate of <40 nm per pulse, the small thermal effect and therefore a potentially high depth resolution capacity.…”
Section: Nuclear Materialsmentioning
confidence: 99%
“…Ablation rate/ laser fluence 16 nm/pulse, 1.7 J/cm 2 (35 ps, 355 nm) (Wcolumnar coating) 40 nm/pulse, 5.3 J/cm 2 (35 ps, 355 nm) (W) [56] 200 nm/pulse, 12 J/cm 2 (35 ps, 355 nm) (W) [56] 500 nm/pulse, 20 J/cm 2 (35 ps, 355 nm) (W) [56] 170 nm/pulse 5.5 J/cm 2 (150 ps,1064 nm) (Mo-W-Al) [44] Operational press. range H isotope distinguishability* Good line separation 2×10 -7 mbar and <5 J/cm 2 (35 ps laser, 335 nm) 3 mbar Ar at 5.5 J/cm 2 (150 ps, 1064 nm) [ From the table and the described experimental work carried out the following conclusions can be made: 1.…”
Section: Ps-libsmentioning
confidence: 99%